Preanalytical mixing of whole-blood specimens in the context of the Athlete Passport. Issue 1 (2nd November 2011) - Ashenden, Michael; Clarke, Anthea; Sharpe, Ken; d'Onofrio, Giuseppe; Allbon, Graeme; Gore, Christopher J
Abstract : Background: Full blood counts are now used as evidence that athletes have used banned blood doping. This has led to legal scrutiny of the efficacy of preanalytical procedures such as specimen homogenisation. Aims: To characterise the impact of different mixing strategies on whole-blood homogeneity. Methods: Manual inversion, mechanical mixing and automatic mixing performed by the Sysmex XT-2000i were evaluated. Results: Automated mixing by the instrument, or 1 min of mechanical mixing, thoroughly homogenised specimens even for tubes that had been refrigerated and left undisturbed for 36 h. Manual inversions were almost as effective, provided that specimens were first allowed to equilibrate to ambient temperatures. Conclusions: Current sport guidelines that mandate at least 15 min of mechanical mixing are excessive. Except where specimens are presented to the instrument manually, mechanical mixing is redundant in the context of full blood counts.